Use of QT Prolonging Medications by Hemodialysis Patients and Individuals Without End‐Stage Kidney Disease. Issue 13 (7th July 2020) - Assimon, Magdalene M.; Wang, Lily; Pun, Patrick H.; Winkelmayer, Wolfgang C.; Flythe, Jennifer E.
Abstract : Background: The rate of sudden cardiac death in the hemodialysis population exceeds that of the general population by >20‐fold. Hemodialysis patients may be particularly susceptible to sudden cardiac death provoked by drug‐induced QT prolongation because of their substantial cardiovascular disease burden, exposure to electrolyte shifts during dialysis, and extensive polypharmacy. However, population‐specific data regarding the frequency and patterns of QT prolonging medication use are limited. Methods and Results: We conducted a descriptive drug utilization study using 3 administrative databases, the United States Renal Data System, MarketScan, and Medicare claims. We characterized the extent and patterns of QT prolonging medication use by adult hemodialysis patients and individuals without end‐stage kidney disease annually from 2012 to 2016. We also identified instances of high‐risk QT prolonging medication use among hemodialysis patients. In total, 338 515 hemodialysis patients and 40.7 million individuals without end‐stage kidney disease were studied. Annual utilization rates of QT prolonging medications with known torsades de pointes risk in hemodialysis patients were 1.4 to 2.5 times higher than utilization rates in individuals without end‐stage kidney disease. Hemodialysis patients with demographic and clinical risk factors for drug‐induced QT prolongation were exposed to medications with known torsades de pointes risk more often than patients without risk factors. Conclusions: Hemodialysis patients use QT prolonging medications with known torsades de pointes risk more extensively than individuals without end‐stage kidney disease. Given the widespread use and instances of high‐risk prescribing, future studies evaluating the cardiac safety of these drugs in the hemodialysis population are needed.